Variable susceptibility of laboratory strains of Aspergillus nidulans to hygromycin B and other ribosomal antibiotics - S. D. Martinelli; A. Zamir (Fungal Genetics Reports, 1987)
Variable susceptibility of laboratory strains of Aspergillus nidulans to hygromycin and other ribosomal antibiotics.